Aerobic Capacity Profile (Vo₂Max) of Novice Athletes Aged 18-19 Years at the Pencak Silat Student Activity Unit - Eko Hernando; Garry William Dony; Cahyo Nugroho Sigit (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aimed to assess VO₂max using the bleep test in 33 SAU pencak silat athletes, comprising 17 male novice athletes and 16 female novice athletes aged 18–19 with survey design. The results of the VO₂max measurements in male and female novice pencak silat athletes showed that the majority of athletes had low aerobic capacity, particularly among male athletes, total of 58.82% of athletes are classified as very poor, followed by 29.41% in the poor category, and only 11.76 % reach the fair category, with (mean ± SD) of (32.9 ml/kg/min ± 3.68), were female athletes,  total of 31.25 % of athletes were in the very poor category, 50.00 % were in the poor category, and 18.75 % of female athletes were in the fair category with (29.9 ml/kg/min ± 3.14). These findings indicate that the cardiorespiratory fitness levels of both male and female athletes remain below recommended fitness standards, thus requiring a more structured endurance training programme.